Effects of Different Doses of Dex Anesthesia on Inflammatory Factors and Hemodynamics in Patients Undergoing Neurosurgery and Its Relationship with RSS Score. (5th October 2022) - Lu, Qiaoling; Wu, Chengwei; Wu, Zhenhua; Wang, Xinbin; Cheng, Hao
Abstract : The effects of different doses of dexmedetomidine (Dex) anesthesia on inflammatory factors and hemodynamics in patients undergoing neurosurgery and its relationship with RSS scores are analyzed. A total of 102 patients who received neurosurgery in our hospital from March 2021 to March 2022 are selected. According to different intraoperative Dex dose, the enrolled patients are randomly divided into low-, medium-, and high-dose groups, 34 patients in each group. In this study, hemodynamic indexes, inflammatory factors, anesthesia effect, and the Ramsay sedation scale (RSS) score are compared in each groups. The experimental results show that in neurosurgery, compared with low-dose Dex, high-dose Dex can better maintain patients' intraoperative hemodynamic parameters and effectively inhibit postoperative inflammatory response, but postoperative awakening time is also relatively prolonged, while medium-dose Dex can effectively control patients' awakening time.